Faktor – Faktor Yang Berhubungan Dengan Kinerja Kader Jumantik Di Wilayah Kerja Puskesmas Segala Mider Lampung Tengah Tahun 2019 - aila karyus (Jurnal Ilmu Kesehatan Masyarakat Indonesia (JIKMI), 2020)
AbstractIn Indonesia (2017), ABJ continues to descrease from national target > 95% in 2017 on be achieved 46,7%. In Province Lampung (2018), ABJ only reached 75%. In Lampung Tengah these ABJ (2018) lower than in 2017 namely 78% and the community health centre, ABJ community health centre continued to decline only reached 78% from standard national > 95%. The low percentage of less than optimal ABJ caused by performance of cadres to dengue control activities. The research aims to observe the factors related to performance of cadres in the community health centre Segala Mider Lampung Tengah in 2019. This was an analytical survey quantitative study with cross sectional desaign. The results showed there was correlation between knowledge (p-value = 0,046, OR = 7,000), attitude (p-value = 0,011, OR = 12,250), motivation (p-value = 0,039, OR = 7,000), the availability tools (p-value = 0,026, OR = 10,000), and reward or salary (p-value = 0,023, OR = 10,000) with performance cadres in the community health centre Segala Mider. The suggestion for community health centre Segala Mider, giving to cadres (jumantik) change for following the training, the procuremnet of banner to increase knowledge, and re-valuete about funding allocations payment for cadres (jumantik).Keywords : Performance of cadres (Jumantik), Knowledge, Attitude, Motivation, Availability tools, and reward or salary.